The role of Applying Six Sigma methodology to Improve the Performance of Bank Account Operations within the framework of the DMAIC Model and Predict the number of Failures using Artificial Neural Networks (ANN). An applied study on the Syrian Real Estate (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to apply the Six Sigma methodology according to the DMAIC model on banking operations, in the Bank Accounts Department of the Syrian Real Estate Bank, Tishreen Branch. By applying Six Sigma tools and techniques, according to the stages of the DMAIC model. Then, Artificial Neural Networks (ANN) was used to predict future failures for 24 months, based on the results obtained from applying Six Sigma methodology. The study spanned 58 months, including 12 months to assess the prevailing situation in the bank, and 46 months of actual application. The research found that the application of Six Sigma methodology led to a decrease in the number of failures from 556 to 38 cases, and thus a decrease in the failure rate from 48.9% to 4.3%. The sigma level increased from 2.9031 to 4.0364, and thus the process efficiency increased from 91.8498% to 99.2817%. The application of Artificial Neural Networks (ANN) to predict future failures has shown that it will decrease within 24 months from 38 cases to 3 cases.